(untitled) (Global Journal of Management and Business Research, 2022)
Business intelligence is a set of tools and techniques which are used to analyze and convert raw data into actionable and coherent insights. This study reveals how BI affects the business performance of banking sector and how banking sector utilized BI in their day-to-day operations. The deductive approach was used as research method and the stratified sampling method was used to determine the sample of this study. Data has been collected by covering twenty-eight state and non-state banks in Sri Lanka. The multiple regression and correlation were used as main analytical techniques to obtain the results. Based on the finding of this study, it has been concluded that there is positive relationship between business intelligence factors ((perception, product, process, team and technology)) and the Business performance and there is significant impact of Business intelligence on the business performance of banking sector in Sri Lanka.